Pelaksanaan Kewenangan Desa Dalam Penertiban Tamu Yang Datang Menurut Undang-Undang Nomor 6 Tahun 2014 Tentang Desa (Studi di Desa Kembang Mekar Sari Kabupaten Indragiri Hilir) - Jusmadi; Jamri; Kms. Novyar Satriawan Fikri (PT PUSTAKA CENDEKIA GROUP, 2026)
This study examines the implementation of village authority in regulating guests arriving in Kembang Mekar Sari Village, Indragiri Hilir Regency, based on Law Number 6 of 2014 concerning Villages. This research is motivated by the suboptimal implementation of guest regulation within the village and the absence of specific regulations in the form of Village Regulations (Perdes) governing the reporting obligation for guests arriving and staying in the village. This study aims to determine the implementation of village government authority in regulating guests, the factors influencing its implementation, and the village government's efforts to overcome obstacles to the implementation of guest regulation in Kembang Mekar Sari Village, Indragiri Hilir Regency. The type of research used is sociological legal research with a descriptive analytical nature. Data sources consist of primary and secondary data. Primary data were obtained through interviews with the Village Head, village officials, RT/RW heads, community leaders, and residents of Kembang Mekar Sari Village, Indragiri Hilir Regency. Secondary data were obtained through a literature review of laws and regulations, books, and journals related to the research. Data analysis was conducted qualitatively using deductive inference. The results indicate that the Village Government's authority to regulate guests has been implemented through an appeal to the community to report guests who stay more than 24 hours to the Head of the local RT/RW. However, this implementation has not been optimal due to the absence of a Village Regulation specifically governing the mechanism for regulating guests, resulting in informal implementation and lack of clear legal certainty. Factors influencing the implementation of guest regulation include legal factors, village government officials, community awareness, facilities and infrastructure, and the community's legal culture. The village government's efforts to overcome these obstacles include community outreach, increased coordination with the RT/RW, enhanced neighborhood security, guest administration data collection, and plans to establish a Village Regulation regarding guest regulation as a form of implementing village-scale local authority.